MTA-Enriched Polymeric Scaffolds Enhanced the Expression of Angiogenic Markers in Human Dental Pulp Stem Cells. (21st February 2022) - Alipour, Mahdieh; Aghazadeh, Zahra; Hassanpour, Mehdi; Ghorbani, Marjan; Salehi, Roya; Aghazadeh, Marziyeh
Abstract : Revascularization of the pulp tissue is one of the fundamental processes and challenges in regenerative endodontic procedures (REPs). In this regard, the current study is aimed at synthesizing the mineral trioxide aggregate- (MTA-) based scaffolds as a biomaterial for REPs. Poly ( ε -caprolactone) (PCL)/chitosan (CS)/MTA scaffolds were constructed and evaluated by FTIR, SEM, XRD, and TGA analyses. Proliferation and adhesion of human dental pulp stem cells (hDPSCs) were assessed on these scaffolds by scanning electron microscopy (SEM) and MTT assays, respectively. The expression of angiogenic markers was investigated in gene and protein levels by real-time PCR and western blotting tests. Our results indicated that the obtained appropriate physicochemical characteristics of scaffolds could be suitable for REPs. The adhesion and proliferation level of hDPSCs were significantly increased after seeding on PCL/CS/MTA scaffolds. The expression levels of VEGFR-2, Tie2, and Angiopoietin-1 genes were statistically increased on the PCL/CS/MTA scaffold. In support of these findings, western blotting results showed the upregulation of these markers at protein levels in PCL/CS/MTA scaffold (P < 0.05 ). The current study results suggested that PCL/CS/MTA scaffolds provide appropriate structures for the adhesion and proliferation of hDPSCs besides induction of the angiogenesis process in these cells.